2009
DOI: 10.1194/jlr.r800034-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

The metabolism and anti-atherogenic properties of HDL

Abstract: Population studies have shown that plasma HDL levels correlate inversely with cardiovascular disease risk. In recent years there has been intense interest in developing strategies for exploiting these cardioprotective properties by increasing HDL levels. While this approach has considerable merit, it is important to recognize that HDL are structurally and functionally diverse and consist of numerous, highly dynamic subpopulations of particles that do not all inhibit atherosclerosis to the same extent. For this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
215
0
12

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(239 citation statements)
references
References 52 publications
6
215
0
12
Order By: Relevance
“…The present experiments could demonstrate that HNF4␣ shRNA-infected cells resulted in the reduced capacity of intestinal Caco-2 cells to produce HDL and its major protein component, apoA-I. Various investigations reported that HDL and apoA-I protect against the development of atherosclerosis by mediating reverse cholesterol transport, a pathway by which excess cholesterol is removed from peripheral cells such as plaque macrophages to the liver for excretion (74,75). Subsequently, HDL and apoA-I were shown to inhibit inflammatory and oxidative damage, a situation in concordance with our observations depicting a lower output of HDL and apoA-I along with pro-inflammatory and pro-oxidant events in HNF4␣-depleted Caco-2 cells.…”
Section: Discussionmentioning
confidence: 79%
“…The present experiments could demonstrate that HNF4␣ shRNA-infected cells resulted in the reduced capacity of intestinal Caco-2 cells to produce HDL and its major protein component, apoA-I. Various investigations reported that HDL and apoA-I protect against the development of atherosclerosis by mediating reverse cholesterol transport, a pathway by which excess cholesterol is removed from peripheral cells such as plaque macrophages to the liver for excretion (74,75). Subsequently, HDL and apoA-I were shown to inhibit inflammatory and oxidative damage, a situation in concordance with our observations depicting a lower output of HDL and apoA-I along with pro-inflammatory and pro-oxidant events in HNF4␣-depleted Caco-2 cells.…”
Section: Discussionmentioning
confidence: 79%
“…Interestingly, a vast number of studies of HDL have suggested a list of expanded activities for the lipoprotein beyond simply contributing as a cholesterol carrier from tissues to liver. This includes anti-inflammatory, anti-parasitic, anti-apoptotic, and innate immune activities [16][17][18]. As an antiinflammatory molecule it mediates its action with the vascular endothelium and circulating inflammatory cells [16][17][18].…”
Section: Antimicrobial and Antiviral Activitymentioning
confidence: 99%
“…This includes anti-inflammatory, anti-parasitic, anti-apoptotic, and innate immune activities [16][17][18]. As an antiinflammatory molecule it mediates its action with the vascular endothelium and circulating inflammatory cells [16][17][18]. Apo A-I exhibits its anti-parasitic effect function by forming a complex with apolipoprotein L1, a minor apolipoprotein component of HDL, a parasite-specific lysosomal pore forming protein, a trypanosome lytic factor (Fig.…”
Section: Antimicrobial and Antiviral Activitymentioning
confidence: 99%
“…Firstly, vitamin D influences formation of HDL particles (26,27,28,29,30). Secondly, serum 25(OH)D inhibits adipocyte differentiation and may thereby influence the development of adiposity (9).…”
Section: Potential Mechanismsmentioning
confidence: 99%